Neoadjuvant Chemoradiotherapy Changes the Landscape of Soluble Immune Checkpoint Molecules in Patients With Locally Advanced Rectal Cancer - Liu, Chao; Wang, Peiliang; Sun, Yi; Dou, Xue; Hu, Xiaoyu; Zou, Wenxue; Sun, Yanlai; Hu, Qinyong; Yue, Jinbo (Frontiers in Oncology, 2022)
Background We aimed to investigate clinical implications of specific soluble immune checkpoint molecules (sICMs) in locally advanced rectal cancer (LARC) patients treated with neoadjuvant chemoradiotherapy (nCRT). Methods We prospectively enrolled 30 LARC patients treated with nCRT and collected blood samples from them before, during, and after nCRT for prospective studies. Immune checkpoints often refer to T cell surface molecules influencing the immune response. Immune checkpoints, in the form of a soluble monomeric form, is widely present in blood. In the study, eight immune checkpoint-related plasma proteins, including programmed death-ligand 1 (PD-L1), CD80, CD86, CD28, CD27, glucocorticoid-induced tumor necrosis factor receptor (GITR), GITR ligand (GITRL), and inducible T-cell costimulator (ICOS), were measured using the Luminex platform. Two independent pathologists categorized patients as the good responders and the poor responders according to Dworak tumor regression grade (TRG). Results Of the 30 patients, the levels of sPD-L1, sCD80, sCD86, sCD28, sGITR, sGITRL, sCD27, and sICOS decreased during nCRT (Pre-nCRT vs. During-nCRT, all p<0.05) but were restored after nCRT treatment (Pre-nCRT vs. Post-nCRT, all p>0.05). In the 14 good responders, the levels of sICMs, other than sGITR (p=0.081) and sGITRL (p=0.071), decreased significantly during nCRT (Pre-nCRT vs. During-nCRT, p<0.05), but they were all significantly increased after nCRT (During-nCRT vs. Post-nCRT, all p<0.05). In the 16 poor responders, only sCD80 was significantly reduced during nCRT (Pre-nCRT vs. During-nCRT, p<0.05), and none was significantly increased after nCRT (During-nCRT vs. Post-nCRT, all p<0.05). High levels of sICMs before nCRT were associated with poor response (all OR≥1). The Pre-model that incorporated the 8 sICMs before nCRT yielded a good predictive value (AUC, 0.848) and was identified as an independent predictor of treatment response (OR, 2.62; 95% CI, 1.11-6.18; p=0.027). Conclusion Our results suggest chemoradiotherapy could influence the change of sPD-L1, sCD80, sCD86, sCD28, sGITR, sGITRL, sCD27, and sICOS in patients with LARC. The levels of the majority of soluble immune checkpoint molecules were reduced during nCRT and then restored at the end of nCRT, particularly in patients who responded well to nCRT. Combined baseline sICMs can be developed to predict treatment response.